2011
DOI: 10.1155/2011/294353
|View full text |Cite
|
Sign up to set email alerts
|

Organic-Ruthenium(II) Polypyridyl Complex Based Sensitizer for Dye-Sensitized Solar Cell Applications

Abstract: A new high molar extinction coefficient organic-ruthenium(II) polypyridyl complex sensitizer (RD-Cou) that contains 2,2 ,6,6 -tetramethyl-9-thiophene-2-yl-2,3,5,6,6a,11c-hexahydro1H,4H-11oxa-3a-aza-benzoanthracene-10-one as extended π-conjugation of ancillary bipyridine ligand, 4,4 -dicaboxy-2,2 :6 ,2 -bipyridine, and a thiocyanate ligand in its molecular structure has been synthesized and completely characterized by CHN, Mass, 1 H-NMR, UV-Vis, and fluorescence spectroscopies as well as cyclic voltammetry. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…This can be altered by adding more methane groups that result in expanding the π-conjugation linkers and an increased efficiency of the DSSC [ 224 ]. Giribabu and co-workers synthesized RD-Cou sensitizers and obtained the conversion efficiency of 4.24% using liquid electrolyte, where coumarin moiety was bridged to the pyridyl groups by thiophene, which resulted in the extended π-conjugation and broadening of the metal-to-ligand charge transfer spectra [ 225 ]. They found that the absorption spectrum of RD-Cou dye was centered at 498 nm with a ɛ = 16,046 M − 1 cm − 1 .…”
Section: Previous and Further Improvements In Dsscsmentioning
confidence: 99%
“…This can be altered by adding more methane groups that result in expanding the π-conjugation linkers and an increased efficiency of the DSSC [ 224 ]. Giribabu and co-workers synthesized RD-Cou sensitizers and obtained the conversion efficiency of 4.24% using liquid electrolyte, where coumarin moiety was bridged to the pyridyl groups by thiophene, which resulted in the extended π-conjugation and broadening of the metal-to-ligand charge transfer spectra [ 225 ]. They found that the absorption spectrum of RD-Cou dye was centered at 498 nm with a ɛ = 16,046 M − 1 cm − 1 .…”
Section: Previous and Further Improvements In Dsscsmentioning
confidence: 99%
“…Although the conversion efficiency obtained was not much desirable, the thermal analysis of this dye shows that it is stable upto 220°C. The thermal stability of this sensitizer has the capability to be used for rooftop applications [36].…”
Section: Recent Progress In Metal-based Sensitizers For Dsscsmentioning
confidence: 99%
“…The DSSC device has three major parts: (a) a semiconductor film electrode (ie, anode)—a transparent conducting glass electrode with minute interstices bandgap semiconductor, like the dye‐coated TiO 2 , which acts as a light sensitizer; (b) an electrolyte layer, wherein the dye molecules are encircled with a layer of electrolyte, which has the ability to recompenses for the lost electrons; (c) and counter electrodes (ie, cathode), which are coated with platinum or graphite . Dyes that are used as sensitizers for the DSSCs must satisfy the following conditions: (a) the dyes absorption spectra must include a broad light spectra between visible light to near‐infrared light region, (b) the dye molecules must consist of anchoring groups like the carboxyl and the hydroxyl groups which strongly bind to the semiconductor oxide surfaces and facilitate the injection of the electrons into the conduction wide‐band gaps of the semiconductor oxide from the dyes, and (3) the dye sensitizers must be well‐balanced for a long period of usage . Furthermore, the energy levels of all molecules, electrolytes, and the semiconductor oxide assist the addition of the electrons and the dye regeneration from the electrolytes …”
Section: Introductionmentioning
confidence: 99%